Constructing the ’Foreign’: Stereotypes in Western Reporting on China and India: A Content Analysis of German and U.S. Newspapers - Albrecht, Gianna; Gayler, Judith; Hanenberg, Marla; Hermanutz, Steven; Ködel, Susanne (Global Media Journal - German Edition, 2024)
Foreign reporting plays a significant role in shaping our perspectives on other countries. However, reporting on non-Western countries is still heavily influenced by Western perspectives, which can lead to distortions, one-sided portrayals, and stereotyping. This study aims to analyze the emergence of stereotypes in U.S. and German reporting on China and India. To this end, two leading national daily newspapers from the USA (Washington Post and New York Times) and Germany (Süddeutsche Zeitung and Frankfurter Allgemeine Zeitung) were examined for their coverage of China and India. The results reveal that stereotypes are more prevalent in the reporting on India across all newspapers. Both countries used political stereotypes to a similar extent, with economic stereotypes being the second most common in coverage of China, while stereotypes about the population dominated the articles on India.